Effect of Current Variation on the Mechanical Properties and Microstructure of GTAW-Welded SS400 Steel - Hasan Hasan; Muchammad Chusnan Aprianto; Johan Maulana; Epa Rosidah Apipah; Ghany Heryana; Amir Amir (TURBO [Tulisan Riset Berbasis Online], 2025)
Gas Tungsten Arc Welding (GTAW) or Tungsten Inert Gas (TIG) Welding employs a tungsten electrode and argon shielding gas to protect the molten metal from atmospheric contamination, resulting in strong and permanent joints. SS400 steel, widely used due to its favorable mechanical properties, can be welded using this method. However, weld quality is strongly influenced by variations in welding current. Too low a current leads to shallow penetration, while excessive current may cause defects and microstructural damage. This study aims to analyze the effect of GTAW current variation on the tensile strength, hardness, and microstructure of SS400 steel with different thicknesses (1.2 mm, 5 mm, and 6 mm). A total of 27 specimens were tested using an experimental method. Tensile strength was evaluated with a universal testing machine, hardness was measured using the Rockwell test, and microstructure was analyzed through metallography. The results show that hardness and tensile strength values are affected by the combination of welding current and plate thickness. Lower current increases hardness, while higher current reduces it. Yield strength and tensile strength decrease with increasing current and thickness due to higher heat input, while elongation varies depending on plate conditions. The microstructure reveals that martensite forms only in medium-thickness plates (5 mm), whereas thin and thick plates are dominated by ferrite and pearlite with grain growth at higher currents.